2016
DOI: 10.5194/gmd-9-3655-2016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of resolving the Rossby radius at mid-latitudes in the ocean: results from a high-resolution version of the Met Office GC2 coupled model

Abstract: Abstract. There is mounting evidence that resolving mesoscale eddies and western boundary currents as well as topographically controlled flows can play an important role in air-sea interaction associated with vertical and lateral transports of heat and salt. Here we describe the development of the Met Office Global Coupled Model version 2 (GC2) with increased resolution relative to the standard model: the ocean resolution is increased from 1/4 to 1/12 • (28 to 9 km at the Equator), the atmosphere resolution in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
82
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 51 publications
8
82
3
Order By: Relevance
“…Less energetic currents and eddies can cause biases in e.g., the strength of overturning circulations [3], oceanic heat uptake [4], and mixed-layer depth [5] as well as model drifts [6]. To understand what sets the energy levels in ocean models at different horizontal resolutions and what parameterisations may be needed, we must understand how KE is transfered between length scales.…”
Section: Introductionmentioning
confidence: 99%
“…Less energetic currents and eddies can cause biases in e.g., the strength of overturning circulations [3], oceanic heat uptake [4], and mixed-layer depth [5] as well as model drifts [6]. To understand what sets the energy levels in ocean models at different horizontal resolutions and what parameterisations may be needed, we must understand how KE is transfered between length scales.…”
Section: Introductionmentioning
confidence: 99%
“…At this grid spacing, the first baroclinic Rossby radius is resolved only near the equator (Hallberg 2013). Hewitt et al (2017) reviewed the improvements found in going toward eddy-poor/ eddy-rich regimes (1/4°-1/10°), with important consequences for large-scale biases (McClean et al 2011;Delworth et al 2012;Small et al 2014a;Hewitt et al 2016), heat uptake (e.g., Griffies et al 2015;Kuhlbrodt et al 2015), and ocean marine ecosystems (Saba et al 2016;McKiver et al 2015;Stock et al 2011). Coupled simulations with ocean resolutions up to 1/16° will enable investigation of the impact of eddies on the mean state and variability of the coupled system.…”
Section: Future Prospects and Challengesmentioning
confidence: 99%
“…We follow a similar strategy to introduce ice-shelf-ocean interactions into the NEMO framework (Madec and the NEMO team, 2016). The work is a first step towards adding an ice sheet component and its interaction within NEMO, and including these interactions within climate models such as IPSL (Dufresne et al, 2013), the Hadley Centre models (Hewitt et al, 2011(Hewitt et al, , 2016, EC earth (Hazeleger et al, 2010), CNRM (Voldoire et al, 2013) and CMCC (Scoccimarro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%